(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the causes of air pollution and its negative effects on human health and the environment. The main sources of air pollution—industrial enterprises, motor vehicles, and energy systems—are examined in detail. In addition, measures being taken to address ecological problems are also considered. The study compares global trends with the situation in Uzbekistan and discusses ways to achieve sustainable development.